Tratamiento de la artritis reumatoidea con un enfoque holístico - Torres Apolo, Vanessa Katherine (Machala : Universidad Técnica de Machala, 2024)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by persistent joint inflammation, leading to pain, stiffness, and progressive disability. This multidimensional approach seeks not only to control symptoms but also to identify and address the underlying causes of the disease, promote balance and harmony in the body, and encourage a healthy lifestyle. One of the fundamental pillars of the holistic treatment of RA is conventional pharmacological therapy. Disease-modifying antirheumatic drugs (DMARDs), such as methotrexate, angiotensin-converting enzyme inhibitors (ACEIs), are widely used to control inflammation. Objective: To analyze the efficacy and safety of complementary and alternative therapies (CATs) as adjuncts to conventional pharmacological treatment in rheumatoid arthritis and to examine the role of psychological interventions, such as cognitive-behavioral therapy and pain management, in coping with rheumatoid arthritis and reducing emotional impact through an academic review of articles in high-impact journals to develop new models of therapies or reinforce existing ones. Methodology: Descriptive, qualitative academic research with scientific support using MESH (Medical Subject Headings) terminology and subsequent investigation in open-access databases such as PUBMED, GOOGLE SCHOLAR, and quartile I scientific journals such as The Lancet Rheumatology, RMD Open, Annals of the Rheumatic Diseases, among others, to provide effective information.
La artritis reumatoide (AR) es una enfermedad autoinmune crónica que se caracteriza por una inflamación persistente de las articulaciones, lo que conduce a dolor, rigidez y discapacidad progresiva. Este enfoque multidimensional busca no solo controlar los síntomas, sino también identificar y abordar las causas subyacentes de la enfermedad, promover el equilibrio y la armonía en el organismo, y fomentar un estilo de vida saludable. Uno de los pilares fundamentales del tratamiento holístico de la AR es la terapia farmacológica convencional. Los medicamentos antirreumáticos modificadores de la enfermedad (FAMEs), como el metotrexato, los inhibidores de la enzima convertidora de angiotensina (IECA), son ampliamente utilizados para controlar la inflamación. Objetivo general: Analizar la eficacia y seguridad de las terapias complementarias y alternativas (TCA) como adyuvantes al tratamiento farmacológico convencional en la artritis reumatoide y examinar el papel de las intervenciones psicológicas, como la terapia cognitivo-conductual y el manejo del dolor, en el afrontamiento de la artritis reumatoide y la reducción del impacto emocional mediante una revisión académica de artículos en revistas de alto impacto con el fin de desarrollar nuevos modelos de terapias o el refuerzo de las existentes. Metodología: Investigación académica de tipo descriptiva, cualitativa, con sustento científico mediante el uso de terminología MESH (Medical Subject Headings) y posterior indagación en bases de datos de acceso libre como PUBMED, GOOGLE SCHOLAR y en revistas científicas de cuartil I como The Lancet Rheumatology, RMD Open, Annals of the Rheumatic Diseases, entre otras, con la finalidad de brindar una información eficaz.
Keywords: ARTRITIS REUMATOIDE; ENFOQUE HOLISTICO; TRATAMIENTO DE LA ARTRITIS REUMATOIDE